Recent weakening of carbon-water coupling in northern ecosystems - Fubo Zhao; Wenbo Shi; Jingfeng Xiao; Meng Zhao; Xing Li; Yiping Wu (npj Climate and Atmospheric Science)
Abstract The terrestrial carbon and water cycles are deeply intertwined, and their coupling is critical to shaping ecosystem processes and land-atmosphere feedback. Understanding how the carbon-water coupling (CWC) changes, which remains rarely explored, is essential for predicting eco-hydrological responses to climate change. Here, using data from eddy covariance towers and remote sensing, we demonstrate a substantial decline in the CWC strength—measured as the correlation between gross primary production and evapotranspiration—across northern ecosystems over the past two decades. This weakening is primarily driven by rising CO₂ levels, with temperature, solar radiation, and precipitation playing secondary roles. Land surface models in the TRENDY project fail to capture this weakening synchronization, primarily due to their inadequate representation of the effects of elevated atmospheric CO2 levels. The weakening of this synchronous variation between water and carbon may signify that the ecosystems are reshaping their eco-hydrological balances across the Northern Hemisphere.